The World Health Organization Classification of Odontogenic Lesions: A Summary of the Changes of the 2022 (5th) Edition - Merva SOLUK-TEKKESIN; John M. WRIGHT (Federation of Turkish Pathology Societies, 2022)
The 5th edition of the World Health Organization (WHO) Classification of Head and Neck Tumors opened to online access in March 2022. This edition is conceptually similar to the previous classification of odontogenic lesions. The only newly defined entity in odontogenic lesions is adenoid ameloblastoma, which is classified under benign epithelial odontogenic tumors. While not odontogenic, the surgical ciliated cyst is a new entry to the cyst classification of the jaws. In other respects, a very important change was made in the new blue books that added "essential and desirable diagnostic criteria" for each entity to highlight the features considered indispensable for diagnosis. In this article, we review the odontogenic tumors and cysts of the jaw sections of the Odontogenic and Maxillofacial Bone Tumors Chapter, outlining changes from the 2017 WHO classification and summarizing the essential diagnostic criteria and new developments.